ANALISIS REALISASI ANGGARAN DI BIRO UMUM SETPROV KALIMANTAN TIMUR (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2016)
The research objective in writing this paper is to determine the performance of the budget at the General Bureau of East Kalimantan in 2014. The analytical method used is descriptive analysis method is an analysis method in which data have been obtained, compiled, categorized, analyzed, and interpreted objectively in order to obtain an overview of the problems encountered and explain the results perhitungan.Pengukuran percentage gains of the General Bureau of Borneo Setprov Timurdihitung use some formulas that are tailored to the characteristics of the components realization, namely: Percentage achievement Actual and Bugget. The results of the study can be seen from the number of allocations and budget realization, then the performance of the General Bureau of Setprov Kaltim visible from the ability to realize the implementation of the budget in the form of programs and activities. In fiscal year 2010realisasi budget by 81.90% and the fiscal year 2014 amounted to 99.69%, which means an increase in the budget realization average of 1.74% per year budget. Result analysis and discussion of the conclusions made are Strong relationship between budget and actual effect on the performance of public agencies setprov kaltim. General Bureau of goal attainment can be described through the achievement of its strategic objectives during the period of the medium-term and long-term. 2014 is the last year the implementation of the Strategic Plan of the General Bureau of years 2010 - 2014. In fiscal year 2010 budget realization amounted to 84.81% and the fiscal year 2014 amounted to 102.85%, which means an increase in the budget realization by an average of 3.60% per year budget.Keywords: Actual, Budget and General Bureau Setprov Kaltim